Impact of the increase of minimum wage in the colombian economy (2017)
This paper presents an investigation of the literature on the effects of the minimum wage level on macroeconomic variables, mainly inflation and unemployment. The literary review mentioned leads throughout the essays. On the other hand, the current situation of the SMLV will be exposed, highlighting both the efforts made and the shortcomings for the Colombian case.